Gibberellin Treatment Accelerates Starch Decomposition and Seed Germination in Sticky Nightshade (Solanum sisymbriifolium Lam.) - Haobo Xu; Danni Mo; Xingyu Zhang; Fangman Li; Jinbao Tao; Pingfei Ge; Yang Yang; Ziyuan Wang; Yuyang Zhang (Horticulturae)
Sticky nightshade (Solanum sisymbriifolium Lam.) is a spiny species with a variety of disease resistance characteristics found worldwide within the Solanum genus. However, its low germination rate and long germination period pose obstacles to the effective use of this species. Here, we treated Sticky nightshade with different concentrations of gibberellin (GA3) and observed paraffin sections of Sticky nightshade seeds treated with different GA3 concentrations over different time ranges. The results showed that a 400 mg/L exogenous GA3 concentration at room temperature could improve the germination rate of Sticky nightshade the most effectively. Exogenous GA3 treatment can significantly accelerate the hydrolysis of starch granules and increase the germination rate of seeds. Subsequently, we also measured the MDA content of Sticky nightshade seeds treated with different GA3 concentrations over different time ranges. The result reveals that GA3 treatment can steadily decrease Sticky nightshade seeds’ MDA content during germination, indicating that exogenous GA3 treatment also reduces membrane peroxidation and maintains the stability of the plasma membrane. In this paper, we identified an optimal GA3-treated concentration of Sticky nightshade to improve seed germination at room temperature and explored the reason why the exogenous GA3 treatment of Sticky nightshade seed increased the germination rate.